2019
DOI: 10.3390/ijerph16091642
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among Industrial Workers in Vietnam and Correlated Factors: A Multi-Site Survey

Abstract: Depressive disorders have been found to be a significant health issue among industrial workers, resulting from work-related factors and causing serious burdens for the workers as well as their employers. Literature on mental health problems of Vietnamese industrial workers has been limited, despite the rapid foreign investment-fueled industrialization process of the country. This study aimed to fill the gap in literature by examining the prevalence of depressive disorders and their potential associated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
4
31
2
1
Order By: Relevance
“…In fact, most of the workers living in this accommodation were migrants from other locals, who might have poor family support or connection [39,44]. On the other hand, living with spouses was associated with a lower likelihood of suicidal ideation, one of the depressive symptoms, confirming the important role of family support in reducing the risk of depressive symptoms as in previous studies [20,25]. However, living with children, especially two children or above, significantly increased the risk of being depressed.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In fact, most of the workers living in this accommodation were migrants from other locals, who might have poor family support or connection [39,44]. On the other hand, living with spouses was associated with a lower likelihood of suicidal ideation, one of the depressive symptoms, confirming the important role of family support in reducing the risk of depressive symptoms as in previous studies [20,25]. However, living with children, especially two children or above, significantly increased the risk of being depressed.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, approximately one-third (30.5%) of industrial workers were identified as positive depressive symptoms, which was much higher than that in the Vietnamese general population (2.8%) [35]. Our finding was comparable to a prior finding among industrial workers in Hanoi and Bac Ninh, Vietnam (38.6%-PHQ-9) [20], but approximately 1.5 times higher compared to workers in shoe-making factories in Hai Phong, Vietnam (18.8%) [25]. In addition, this prevalence was relatively higher than that of factory workers in other developing countries such as Bangladesh (20.9% in garment workers) [8] or India (0% in general factory workers but 36% had anxiety disorders and 18% had stress) [35] but equal to the result in China (31.7% in shoe-making workers) [14] and Malaysia (35.4% in automotive assembly workers) [11].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations